Does Knowing Brand or USDA Grade of Beef Strip Steaks Affect Palatability for Consumers? - A. K. Wilfong; K. V. McKillip; J. M. Gonzalez; T. A. Houser; E. A. Boyle; J. A. Unruh; T. G. O'Quinn (Kansas Agricultural Experiment Station Research Reports, 2016)
In consumers’ eyes, not all beef is considered equal. In addition to USDA quality grades, close to 150 branded beef programs are approved for the segregation and marketing of beef products (USDA, 2015). This large number of product categories allows consumers to have a choice in the products they purchase. Blind sensory panel testing of beef, where consumers are not shown the brand or information about a product, has been used for many years. While important to determine palatability characteristics of beef when evaluated blind, consumers do not select, purchase, and consume beef without additional product information. Evidence suggests that branding and product labeling has an influence on consumers’ decisions before having firsthand experience of the product (Levin and Gaeth, 1988). Branding products allows pieces of information to be used to form quality expectations (Steenkamp and vanTrijp, 1996) and can encourage consumers to pay a premium for the increased quality associated with a brand (Grunert et al., 2004). Moreover, previous research suggests that consumers perceive a product differently when brand information is disclosed (Allison and Uhl, 1964). Numerous studies have evaluated the economic impact of beef branding; however, no research has focused on the effect of branding on consumer perception of beef eating quality. Therefore, our objective was to determine how consumer palatability ratings of beef strip loin steaks are affected when products are identified with a brand or USDA grade.
Keywords: brand; grade; palatability